Design and Development of a New Long-Pulse-Width Power Supply - Kangqiao Ma; Lifeng Zhang; Tianwei Zhang (Energies, 2025)
In order to achieve a long-pulse-width output, a new long-pulse-width modulator based on the charging power supply of LCC-type high-frequency resonant converters and the pulse-generating unit in series IGBT switching technology has been designed. The relationship between the resonant cavity gain and the switching frequency has been derived. In the charging phase, the critical intermittent control mode is used to increase the charging speed, and in the voltage stabilization phase, the hysteresis burst control strategy is used to improve voltage accuracy. The simulation results show that the output pulse amplitude is 10 kV, the pulse width can reach 650 μs, and the top-drop is about 12%. Thus, a long pulse width modulator is developed. The output pulse voltage can reach 4 kV, and the output pulse width is 650 μs. The power supply reduces the capacity of the energy storage capacitor, which has industrial application value.